Preparation and characterization of highy conductive and trasparent SnO2 (F) thin film - Thanh Binh, Le Thi; Duong, Vo Hai; Long, Nguyen Ngoc (VNU Journal of Science: Natural Sciences and Technology, 1996)
Abstract